RFP-based method for real-time tracking of invasive bacteria in a heterogeneous population of cells - Akinsola, Rasaq Olajide; Malik, Adewoyin; Choon, Weng Lee; Edmund Ui Hang, Sim; Kumaran, Narayanan (Elsevier, 2021)
Quantification of bacterial invasion into eukaryotic cells is a prerequisite to unfold the molecular mechanisms of this vector’s function to obtain insights for improving its efficiency. Invasion is traditionally quantified by antibiotic protection assays that require dilution plating and counting of colony-forming units rescued from infected cells. However, to differentiate between attached and internalized bacteria vector, this assay requires supplementation by a time-consuming and tedious immunofluorescence staining, making it laborious and reduces its reliability and reproducibility. Here we describe a new red fluorescent protein (RFP)-based highthroughput and inexpensive method for tracking bacterial adherence and internalization through flow cytometry to provide a convenient and real-time quantification of bacterial invasiveness in a heterogeneous population of cells. We invaded MCF-7, A549, and HEK-293 cells with the E. coli vector and measured RFP using imaging flow cytometry. We found high cellular infection of up to 70.47% in MCF-7 compared to 27.4% and 26.2% in A549 and HEK-293 cells, respectively. The quantitative evaluation of internalized E. coli is rapid and celldependent, and it distinctively differentiates between attached and cytosolic bacteria while showing the degree of cellular invasiveness. This imaging flow cytometry approach can be applied broadly to study host bacteria interaction.